Sierra Leone : Poverty Reduction Strategy Paper. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
This paper examines Sierra Leone's Poverty Reduction Strategy Paper (PRSP). Sierra Leone's PRSP considers a number of short- to medium-term challenges that should not only impact immediately on the living conditions of people but also lay solid foundations for addressing the long-term causes of conflict and poverty. These have been identified through extensive national consultations. In addition, the PRSP also considers a number of short-term challenges that need to be met immediately.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet